Study on scatter in mechanical properties of cylinder head with complex structure characters. (May 2022) - Li, Dong-wei; Huang, Wei-qing; Liu, Jin-xiang; Ren, Pei-rong; Zuo, Zheng-xing; Zhang, Ling-jun
Graphical abstract: Highlights: The microstructure affects the scatter of mechanical properties. The scatter of mechanical properties is characterized quantitatively. The scatter of mechanical properties relating to the spatial region of cylinder head is different. Uneven distribution of pores is the major reason for the scatter of mechanical properties. The established model based on the pore information predicts fatigue life well. Abstract: The scatter of casting defects induced by the casting process causes the scatter of mechanical properties of cast alloys. The cylinder head of a high-power density engine is huge and complex, which frequently leads to fatigue behavior due to scattering and uncertainty of casting defects. A statistical approach is used to examine the mechanical properties at multiple places of a cylinder head with a complicated construction, including the top plate, the connecting wall, and the bottom plate, in order to determine the scatter of casting defects. A prediction model is built based on the pore of fatigue crack initiation and predicts the fatigue life well. The findings show that the grain size scatters at different positions of the cylinder head correspond to tensile properties, while porosity scatters at the crack initiation site of fracture specimens from different positions of the cylinder head correspond to fatigue life. As a result, the microstructure of the complicated cylinder head at different sites is a major element influencing the spatial scatter of mechanical characteristics, which can be exploited to promote cylinder head optimization.